Conservative Accounting Choices - Bagnoli, Mark; Watts, Susan G. (Management Science, 2005)
Managers have sufficient discretion under generally accepted accounting principles (GAAP) to adopt more or less conservative financial reporting policies. In this paper, we develop a signaling model to provide insight into managers’ decisions to be conservative in their accounting. We provide conditions under which the market can use the manager’s exercise of discretion to infer her private information about the future prospects of the firm and thus firm value. Under these conditions, we also show that there are meaningful differences between earnings response coefficients for firms whose managers choose a conservative reporting policy and those whose managers do not. Finally, we use our theoretical model to provide intuition for some established empirical results on earnings response coefficients.